The microstress effect : how little things pile up and create big problems-and what to do about it - Cross, Robert L., 1967-; Dillon, Karen (Editor) (Boston, Massachusetts : Harvard Business Review Press, 2023)
"There is a force in our everyday lives that we aren't even aware of-and it's so powerful it threatens to derail otherwise promising careers and lives: microstress. It's the hidden epidemic of small moments of anxiety that infiltrate both our work and personal lives. Because each individual microstress is so small, it doesn't trigger the normal stress response in our brains to help us deal with it. Instead, the microstress just embeds in our minds, accumulating along with scores of other microstresses, day-to-day and week-to-week. The long-term effect is devastating: microstress invisibly weighs us down, damages our physical and emotional health, and contributes to a decline in our overall well-being. What's more, microstress is baked into our lives. The source of microstress is seldom a classic antagonist, such as a demanding client or jerk boss. Instead, it comes from the people-in and out of work-with whom we are closest: our friends, family, and colleagues. The good news is that once you learn about microstress, you can fight back. Drawing on fresh research, Rob Cross and Karen Dillon will teach you how to recognize and manage the most common forms of microstress, and even remove some from your life. Compelling interviews with high achievers who've endured their share of microstress bring to life best practices that show you how to build resilience against microstress, and ultimately how to find purpose in your everyday life, using it as an antidote to your own microstress. It's time to break free from the microstress that's stealing your life. Start here"--
A Crisis of Well Being -- Why You Can't Keep Up Anymore -- Why Others Drain Your Energy -- Why You Don't Feel Like You -- Best Practices from The Ten Percenters -- How to Build Resilience -- How to Stay Healthy -- How to Find Your Purpose.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 03, 2023).
WorldCat record variable field(s) change: 050
Keywords: Stress (Psychology); Job stress; Resilience (Personality trait); Adjustment (Psychology); Work-life balance; Personality and occupation; Adjustment (Psychology); Job stress; Personality and occupation; Resilience (Personality trait); Stress (Psychology); Work-life balance; elektronické knihy; electronic books